2020
DOI: 10.3390/antiox9060510
|View full text |Cite
|
Sign up to set email alerts
|

Seed Oil from Mediterranean Aromatic and Medicinal Plants of the Lamiaceae Family as a Source of Bioactive Components with Nutritional

Abstract: The potential use as food ingredients of 12 commercial seed species belonging to the Lamiaceae family constitutes the main goal of this research. For that, the oil yield, the lipid profile, tocopherol content, phenolic profile and antioxidant capacities were determined. Seeds from Satureja hortensis, S. montana, Lavandula angustifolia, L. latifolia and Origanum vulgare can be considered as important sources of ω-3 polyunsaturated fatty acids (50.5; 52.4; 52.1; 48.5 and 45.5 g/100 g, respectively), likewise for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 34 publications
1
7
0
1
Order By: Relevance
“…Moreover, interesting amounts of luteolin (9 µg/g oil) and ellagic acid (4 µg/g oil) were recorded. In line with our results, thymol has also been cited recently as the key polyphenolic compound in basil seeds oil (11 mg/100g oil) obtained after extraction through a combination of n-hexane and ethyl acetate [ 2 ].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, interesting amounts of luteolin (9 µg/g oil) and ellagic acid (4 µg/g oil) were recorded. In line with our results, thymol has also been cited recently as the key polyphenolic compound in basil seeds oil (11 mg/100g oil) obtained after extraction through a combination of n-hexane and ethyl acetate [ 2 ].…”
Section: Resultssupporting
confidence: 91%
“…According to Ramadan et al [ 27 ], α-tocopherol (284 µg/mg) and γ-tocopherols (225 µg/g) were the major components in black cumin seed oil. Regarding O. basilicum , γ-tocopherol was identified as being the one quantified at high concentration in seed oil [ 2 , 26 ]. Moreover, it was reported that γ-tocopherol is a characteristic compound in seed oils of species belonging to the Lamiaceae family [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, the importance of aromatic and medicinal plants is recognized worldwide, not only for their curative and preventive properties, but also for their uses in the pharmaceutical and food industries [ 1 ]. The Dehesa of Extremadura is characterized as an ecosystem with great biodiversity where many species of plants considered to be medicinal can be found, and are important in the pharmaceutical industry [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In view of their importance, studies were aimed at breeding plants able to increase the content of bioactive phenols [ 23 ]. The research in the field continues, and more and more plants are investigated for their phenolic content and related bioactivity [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. The antioxidant activity of natural phenols has been related to their scavenger ability towards free radicals [ 42 ].…”
Section: Introductionmentioning
confidence: 99%